Long Pentraxin 3-Mediated Fibroblast Growth Factor Trapping Impairs Fibrosarcoma Growth - Rodrigues, Priscila Fabiana; Matarazzo, Sara; Maccarinelli, Federica; Foglio, Eleonora; Giacomini, Arianna; Silva Nunes, João Paulo; Presta, Marco; Dias, Adriana Abalen Martins; Ronca, Roberto (Frontiers in Oncology, 2018)
Fibrosarcomas are soft tissue mesenchymal tumors originating from transformed fibroblasts. Fibroblast growth factor-2 (FGF2) and its tyrosine-kinase receptors (FGFRs) play pivotal roles in fibrosarcoma onset and progression, FGF2 being actively produced by fibroblasts in all stages along their malignant transformation to the fibrosarcoma stage. The soluble pattern recognition receptor long pentraxin-3 (PTX3) is an extrinsic oncosuppressor whose expression is reduced in different tumor types, including soft tissue sarcomas, via hypermethylation of its gene promoter. PTX3 interacts with FGF2 and other FGF family members, thus acting as a multi-FGF antagonist able to inhibit FGF-dependent neovascularization and tumor growth. Here, PTX3 overexpression significantly reduced the proliferative and tumorigenic potential of fibrosarcoma cells in vitro and in vivo. In addition, systemic delivery of human PTX3 driven by the Tie2 promoter inhibited the growth of fibrosarcoma grafts in transgenic mice. In a translational perspective, the PTX3-derived small molecule FGF trap NSC12 prevented activation of the FGF/FGFR system in fibrosarcoma cells and reduced their tumorigenic activity in vivo. In conclusion, impairment of the FGF/FGFR system by FGF trap molecules may represent a novel therapeutic approach for the treatment of fibrosarcoma.